2007
DOI: 10.1007/s11661-007-9169-7
|View full text |Cite
|
Sign up to set email alerts
|

A Quest for a New Hot Tearing Criterion

Abstract: Hot tearing remains a major problem of casting technology despite decades-long efforts to develop working hot tearing criteria and to implement those into casting process computer simulation. Existing models allow one to calculate the stress-strain and temperature situation in a casting (ingot, billet) and to compare those with the chosen hot tearing criterion. In most successful cases, the simulation shows the relative probability of hot tearing and the sensitivity of this probability to such process parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(99 citation statements)
references
References 26 publications
1
98
0
Order By: Relevance
“…It is commonly assumed that the dendrites start to bridge together when the solid fraction reaches approximately 98 pct if the eutectic temperature is not yet reached. [5,15,16] Therefore, the integral limits for the A parameter in Eq. [5] are from the point where the solid fraction f s = 0.98, i.e., the so-called coherency temperature, to the liquidus temperature.…”
Section: E the Hot Cracking Susceptibility Modelmentioning
confidence: 99%
“…It is commonly assumed that the dendrites start to bridge together when the solid fraction reaches approximately 98 pct if the eutectic temperature is not yet reached. [5,15,16] Therefore, the integral limits for the A parameter in Eq. [5] are from the point where the solid fraction f s = 0.98, i.e., the so-called coherency temperature, to the liquidus temperature.…”
Section: E the Hot Cracking Susceptibility Modelmentioning
confidence: 99%
“…Based on the alloy microstructure shown in Figure 6.7, it will be observed that the severity of shrinkage porosity and hot cracking may be reduced significantly upon the hot-tearing crack initiates from a pore or a series of pores in conditions of non-uniform thermal contraction of the coherent dendrites. 94 Such parallelism may also be explained by the deteriorating effect caused by the limited feedability and the diminished permeability of the mushy zone leading to the formation of high levels of porosity and to the difficulties It should be mentioned that the Bl Si-alloy is not covered by this equation. These results which were illustrated in the preceding three figures may help to explain the beneficial role of the grain refining additions, namely Zr-Ti and Ti, in reducing the hot-tearing susceptibility of the Al-2wt%Cu base alloy.…”
Section: Effects Of Mold Temperaturementioning
confidence: 99%
“…High cooling rates and non-equilibrium solidification conditions of the DC-casting result in the formation of nonequilibrium eutectics and intermetallics, which mainly precipitate on the grain boundaries and interdendritic spaces during final stages of solidification [2,3]. The formation of such phases coincides with the appearance of thermal stresses when the dendritic grains start to form a coherent network [4]. Due to their low melting point, the non-equilibrium eutectics provide potential nucleation sites and propagation paths for hot cracking (cracking above the solidus) while they are still in the liquid state.…”
Section: Introductionmentioning
confidence: 99%